2016
DOI: 10.2147/dddt.s117806
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prostaglandin glaucoma drops on platelet-activating factor action: an in vitro study

Abstract: AimThe aim of this study was to investigate the effect of different prostaglandin analogs on platelet-activating factor (PAF) levels.MethodsThree prostaglandin analogs were selected: bimatoprost 0.3 mg/mL, latanoprost 50 μg/mL, and tafluprost 15 μg/mL. Each drug sample was tested for its ability to cause platelet aggregation, which was measured as PAF-induced aggregation, before and after the addition of various concentrations of the examined sample, creating a linear curve of percentage inhibition (ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…There is evidence of cytoskeletal modulation by rho kinase inhibitors, 76 whereas latanoprost has been shown to increase phosphoinositide turnover following binding with FP receptors in human trabecular meshwork and rat vascular smooth muscle cells. 77 79 Additionally, latanoprost can also affect platelet activity factor in rabbit blood 80 and endothelin receptors of human choroidal melanocytes. 81 A recently published study from our laboratory 82 has found that the IOP-lowering effect of latanoprost is mediated by signaling through stanniocalcin-1 (STC-1) and that STC-1 by itself can mimic the ocular hypotensive effect of latanoprost.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of cytoskeletal modulation by rho kinase inhibitors, 76 whereas latanoprost has been shown to increase phosphoinositide turnover following binding with FP receptors in human trabecular meshwork and rat vascular smooth muscle cells. 77 79 Additionally, latanoprost can also affect platelet activity factor in rabbit blood 80 and endothelin receptors of human choroidal melanocytes. 81 A recently published study from our laboratory 82 has found that the IOP-lowering effect of latanoprost is mediated by signaling through stanniocalcin-1 (STC-1) and that STC-1 by itself can mimic the ocular hypotensive effect of latanoprost.…”
Section: Discussionmentioning
confidence: 99%
“…Additional disease‐linkage studies showed that the expression of the PAF catabolic enzyme, PAF‐acetyl hydrolase (PAF‐AH), was significantly elevated in retinas of diabetic rats 106 . And, this seemed to translate to clinical studies since plasma PAF‐AH was also up‐regulated in diabetic patients with proliferative retinopathy 107 . However, whether these observations were causal or consequential of the disease remains to be determined.…”
Section: Role Of Paf In Ocular Diseasesmentioning
confidence: 99%
“… 106 And, this seemed to translate to clinical studies since plasma PAF‐AH was also up‐regulated in diabetic patients with proliferative retinopathy. 107 However, whether these observations were causal or consequential of the disease remains to be determined. Nevertheless, PAF seems to be a contributor to the pathological milieu of factors and processes in retinal diseases and perhaps PAF receptor antagonist can have a role in mitigating some signs and symptoms associated with diabetic retinopathy, ROP and age‐related macular degeneration (AMD).…”
Section: Role Of Paf In Ocular Diseasesmentioning
confidence: 99%